1998
DOI: 10.1046/j.1365-2869.1998.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed sleep phase syndrome: A placebo‐controlled cross‐over study on the effects of melatonin administered five hours before the individual dim light melatonin onset

Abstract: SUMMARYIn a double-blind placebo-controlled cross-over study, 30 patients with Delayed Sleep Phase Syndrome (DSPS) were included, of whom 25 finished the study. Melatonin 5 mg was administered during two weeks in a double-blind setting and two weeks in an open setting successively or interrupted by two weeks of placebo. The study's impact was assessed by measurements of the 24-h curves of endogenous melatonin production and rectal temperature (n=14), polysomnography (n=22), actigraphy (n=13), sleep log (n=22),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
114
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(118 citation statements)
references
References 5 publications
3
114
0
1
Order By: Relevance
“…We included nineteen studies involving a total of 1683 subjects in this meta-analysis [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. From the search on Pubmed and related bibliography above described 268 studies were selected.…”
Section: Included Studiesmentioning
confidence: 99%
“…We included nineteen studies involving a total of 1683 subjects in this meta-analysis [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. From the search on Pubmed and related bibliography above described 268 studies were selected.…”
Section: Included Studiesmentioning
confidence: 99%
“…It is particularly common in adolescents and can be also associated with depression. [67,68] Meta-analysis of the two eligible trials [52,53] investigating the role of melatonin in treating DSPS demonstrated an overall significant improvement in sleep onset latency compared with placebo (total mean difference = -22.05 minutes, 95% CI: -32.02, -12.09). The overall estimated score of melatonin treatment was significant (Z=4.34, P<0.0001) (Fig.3).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Melatonin facilitates achieving better sleep for these patients by reducing the sleep-onset latency [73] or by regulating sleep-wake times to coincide with the natural circulatory cycle, as well as reducing sleep episodes without muscle atonia. [50] The mechanism by which the occurrence of reducing sleep episodes without muscle atonia in RBD is still unknown and requires further study.…”
mentioning
confidence: 99%
“…Melatonin is a nutritional supplement and is not regulated by the Food and Drug Administration (FDA), but is approved for use in treating sleep disorders. Studies involving melatonin are limited by the small number of participants, but studies have shown that administering melatonin (5 mg) 5 hours before sleep onset resulted in advancing sleep onset time [23][24][25].…”
Section: Delayed Sleep Phase Disordermentioning
confidence: 99%